New Forms of Discrete Mechanics - Greenspan, Donald (University of Wisconsin-Madison Department of Computer Sciences, 1971)
Stability limitations, inherent in a previously developed discrete approach to mechanics, are relaxed by introducing two alternative approaches, one explicit and the other implicit. Computer results for motion in a nonlinear force field, planetary motion, nondegenerate three body interaction, and nonlinear string vibration are described and compared.